2022
DOI: 10.1039/d2qi00125j
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic sulfide particles incorporated in Fe/Co-based metal–organic framework ultrathin nanosheets toward boosted electrocatalysis of the oxygen evolution reaction

Abstract: The development of inexpensive, high-performance, and long-lasting electrocatalysts toward oxygen evolution reaction (OER) proves crucial to enhance the efficiency of water splitting to obtain clean and sustainable energy. Herein, Fe/Co-based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Nickel molybdate (NiMoO 4 ) nanomaterial has attracted considerable interest owing to its rich available catalytically active sites and the convenience of the preparation process. To improve the catalytic activity of NiMoO 4 , various strategies, including morphology regulation, defect engineering, heteroatom doping, and interface engineering, have been developed. Among them, the construction of interface-engineered electrocatalysts via the interface engineering strategy can not only offer a more favorable interface for the adsorption/activation of different active species but also enable interfacial electron transfer between different components, which is expected to enhance the electrocatalytic activity. Accordingly, NiMoO 4 @Co 3 O 4 core–shell nanorods were synthesized by coating a thin Co 3 O 4 layer on NiMoO 4 nanorods using atomic layer deposition, and the obtained heterostructure showed an outstanding OER catalytic activity with a low overpotential of 120 mV at 10 mA cm –2 .…”
Section: Introductionmentioning
confidence: 99%
“…Nickel molybdate (NiMoO 4 ) nanomaterial has attracted considerable interest owing to its rich available catalytically active sites and the convenience of the preparation process. To improve the catalytic activity of NiMoO 4 , various strategies, including morphology regulation, defect engineering, heteroatom doping, and interface engineering, have been developed. Among them, the construction of interface-engineered electrocatalysts via the interface engineering strategy can not only offer a more favorable interface for the adsorption/activation of different active species but also enable interfacial electron transfer between different components, which is expected to enhance the electrocatalytic activity. Accordingly, NiMoO 4 @Co 3 O 4 core–shell nanorods were synthesized by coating a thin Co 3 O 4 layer on NiMoO 4 nanorods using atomic layer deposition, and the obtained heterostructure showed an outstanding OER catalytic activity with a low overpotential of 120 mV at 10 mA cm –2 .…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that once soaking Co-MOF/Fe 10 in an alkaline electrolyte, a large amount of OH – will contact the TPA ligands in Co-MOFs and then react with Co 2+ and Fe 3+ to form CoFe-LDHs in situ. The CoFe-LDHs act as real active species that will be involved in the formation of active intermediates during OER, thereby expediting the whole reaction, in accordance with the available literature. As shown in Figure c,d, SEM and TEM images of Co-MOF/Fe 10 after immersion in 1 M KOH identify the flocculent nanosheet structure, which is favorable to the exposure of more active sites and expedites the formation of O–O bonds. Moreover, the high-resolution TEM image in Figure e displays the distinct lattice stripe with the spacings of 0.287 and 0.251 nm matching with the (012) plane of Co­(OH) 2 and the (120) plane of FeOOH, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, the generated metal sulfides can induce an interface effect with MOFs to regulate the electronic structure of metal ions and increase the binding energy of Ni and Fe (verified by the above XPS analysis), which is more conducive to the OER reaction. 43 In addition, the in situ formed nickel sulfides exists in the form of 0 D quantum dots, which have rich marginal active sites and large specific surface area, which provides the maximum contact with the electrolyte and enhances the electron transport during the catalytic process. 44 Therefore, NSQDs@NiFe-TPA greatly reduced the overpotential compared with pure NiFe-TPA.…”
Section: Resultsmentioning
confidence: 99%
“…reaction. 43 In addition, the in situ formed nickel sulfides exists in the form of 0 D quantum dots, which have rich marginal active sites and large specific surface area, which provides the maximum contact with the electrolyte and enhances the electron transport during the catalytic process. 44 Therefore, NSQDs@NiFe-TPA greatly reduced the overpotential compared with pure NiFe-TPA.…”
Section: Electrocatalytic Performance Of Oermentioning
confidence: 99%